Reformulated reciprocal product degree distance of graphs - Pattabiraman K.; Kaladevi V.; Murugesan R. (Utilitas Mathematica, 2022)
In this paper, we study a new graph invariant named reformulated reciprocal product degree distance R1, which is defined for a connected graph G as (Equation presented) On the other hand, it is also the generalized version of reciprocal product degree distance of a connected graph, which is defined as RDD.(G) = (Equation presented) paper, we present exact formulae for the reformulated reciprocal product degree distance of join, composition, tensor product, strong product of two graphs. Finally, we obtain the reformulated reciprocal product degree distance of double graph. © 2018 Utilitas Mathematica Publishing Inc. All rights reserved.